Smart irrigation using WSN based on IOT - Krishna Anne, VP; R V Siva Naga Durg, Kuricheti; Krishna Muddineni, Rama; Gowtham Peri, Surya (International Journal of Engineering and Technology, 2018)
To set right the usage of water for crops of agriculture an automated irrigation system has been implemented. A moisture soil sensor; and a temperature measure sensor which is called as network of the distributed wireless is used at base of the plant. Along with these, we implemented a gateway unit. which gathers information and regulate it and by activating the triggers actuators, it can send and receive the transmits data to and from the web application. I proposed the algorithm which having the temperature and soil moisture threshold values that embedded in a gate way based on micro controller. It implemented panels of the photovoltaic; and having a duplex communication link; and works with the interface i.e. cellular-Internet which offers that data inspection & irrigation timing. All this can be programmed by using a web page. Implemented automated Crop water saving system tested for 136 days in sage crop field. It can be saved 90% water compared to others. The main 3 advantages of this automated system make it place successfully in any place for 18 months. As it is energy self-rule, cost less, so it can be efficiently useful in limited water geographical lands.